2000
DOI: 10.2175/106143000x137464
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aerobic Digestion by Prethickening, Staged Operation, and Aerobic–Anoxic Operation: Four Full‐Scale Demonstrations

Abstract: Four full-scale aerobic digesters were studied to determine the effects of prethickening, staged operation, and aerobic-anoxic operation on digester performance. Prethickening is expected to enhance aerobic digestion by reducing hydraulic flow rates, thereby allowing increased solids retention time (SRT) values and temperature elevation. Staged operation increases the plug flow characteristic of the digester, resulting in increased solids stabilization and pathogen destruction. Aerobic-anoxic operation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The additional process also decreased odors, filtrate strength and phosphate, and foaming in filtrate. Daigger and Bailey (2000) showed that staged operation and aerobic-anoxic operation improve performance of aerobic digestion. Staged operation (with several aerobic-digestion tanks in series) increases solids stabilization and pathogen destruction.…”
Section: Improv Ing Aerobic Digestionmentioning
confidence: 99%
“…The additional process also decreased odors, filtrate strength and phosphate, and foaming in filtrate. Daigger and Bailey (2000) showed that staged operation and aerobic-anoxic operation improve performance of aerobic digestion. Staged operation (with several aerobic-digestion tanks in series) increases solids stabilization and pathogen destruction.…”
Section: Improv Ing Aerobic Digestionmentioning
confidence: 99%